1981
DOI: 10.1073/pnas.78.7.3986
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of all singly labeled [ 15 N]adenines: Mass spectral fragmentation of adenine

Abstract: Syntheses of all five of the singly labeled ['5N]adenines are now provided. The presence or absence of twobond '5N-'H spin couplings in their 1H NMR spectra confirm the location of the isotope in each case. The fragmentation patterns in their mass spectra are indicative ofthe sequential losses ofHCN units and of CH2N2 from adenine upon electron impact.The synthesis of [6-amino-14N]adenine and [9-'5N]adenine provided useful information concerning the -fragmentation of adenine under electron impact (1). We consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…Sethi et al [15] conclude from studies with isotope labeled adenines that most of the fragmentation pathways exhibit largely random isotopic retention patterns, and that deuterium labeling is inconclusive because of rearrangements of hydrogen prior to expulsion of HCN. The studies of Barrio et al [14] with 15 N labeled adenines combined with the results of Sethi et al [15], show that the formation of 108 u by HCN loss is over 90% site specific for N1 and C2 and 6-8% for C2 and N3. Contrary to this, the populations of M-2(HCN) ions (81 u) and of M-HCN-NH 2 CN ions (66 u) originate from pathways involving initial HCN loss from all the five nitrogen atoms in the molecule.…”
Section: Fragmentation Pathwaysmentioning
confidence: 98%
See 2 more Smart Citations
“…Sethi et al [15] conclude from studies with isotope labeled adenines that most of the fragmentation pathways exhibit largely random isotopic retention patterns, and that deuterium labeling is inconclusive because of rearrangements of hydrogen prior to expulsion of HCN. The studies of Barrio et al [14] with 15 N labeled adenines combined with the results of Sethi et al [15], show that the formation of 108 u by HCN loss is over 90% site specific for N1 and C2 and 6-8% for C2 and N3. Contrary to this, the populations of M-2(HCN) ions (81 u) and of M-HCN-NH 2 CN ions (66 u) originate from pathways involving initial HCN loss from all the five nitrogen atoms in the molecule.…”
Section: Fragmentation Pathwaysmentioning
confidence: 98%
“…Studies with isotope labeled adenines [13][14][15] show that most of the fragmentation pathways exhibit largely random isotopic retention patterns, indicating the presence of multiple fragmentation pathways. Based on this we attribute the rapid rise of these ion yields, with powers p 2, to several onsets very close to each other due to the presence of parallel fragmentation pathways with similar appearance energies.…”
Section: Appearance Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The EI study of adenine showed that the major fragmentation path involves successive loss of HCN molecules. Studies of labeled adenines [29,30] demonstrated that the initially eliminated HCN contains the N1 atom and the loss of the NH 2 group was not observed. For guanine, the initial expulsion of neutral cyanamide (H 2 NCN) is the dominant fragmentation (from the pyrimidine's N1-C2-NH 2 moiety), and some NH 2 group elimination was observed as well.…”
Section: Initial Expulsion Of Nitrile or Ammoniamentioning
confidence: 99%
“…Similar loss of HCN from adenine on fragmentation has been reported using deuterated adenine 36 and using 15 N-labeled adenine. 37 adenine is a pentamer of HCN and it can be formed in interstellar space by oligomerization of HCN. 11,12 Fig .…”
mentioning
confidence: 99%